Multilevel Analysis Association of Soil Transmitted Helminths and Stunting in Children Aged 6-12 Years Old in Pinrang District, South Sulawesi - Muslimah, Putri Andini; Salimo, Harsono; Dewi, Yulia Lanti Retno (Journal of Epidemiology and Public Health, 2020)
Background: Stunting in children is often associated with infectious diseases, one of which is Soil Transmitted Helminths (STH). Worms in child